ANALISIS DAMPAK PENDAMPINGAN ORANG TUA TERHADAP KEPRIBADIAN SISWA SD - Nadila Amalia; Febri Fajar Pratama; Deni Chandra (STKIP Subang, 2025)
This study aims to analyze the impact of parental guidance on the personalityofstudent at SDN Balandongan, Tasikmalaya Regency. The issue raised is thedependence of children on their parents during the learning process, which canaffect their personality develovment. The methodology used is a desciptivequalitative approach, with data collection through observasion, interviews, anddocumentation. The research subjects consist of one second-grade student, theirparents, and the class teacher. The results indicate the intensive parentalguidance significantly influences the students personalities. Children who arealways accompanied then to be less confident, shy, and dependent one theirparentes. In contrast, students who do not receive intensive guidance show amore independent, cheerful personality and are active in interacting with theirpeers and teachers. Furthermore, appropriate guidance can enhance children’sindependence and discipline, while inadequate guidance petterns can hinder theirsocial and emotional development. This research emphasizes the importance ofparental roles in suppoting the development of student personalities, as well as theneed for synergy between parents and school to create a conducive learningenvironment.